2016
DOI: 10.1620/tjem.239.269
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ADP-ribosyltransferase 1 Is Associated with Poor Prognosis of Glioma Patients

Abstract: Glioma has a poor prognosis due to its rapid overgrowth, diffuse invasion, and chemotherapy resistance. The improvements in clinical outcome are still limited and the identification of novel biomarkers involved in the progression of gliomas is still under critical demands. Amino acid ADP-ribosyltransferase 1 (ART1) is an enzyme that catalyzes the mono-ADP-ribosylation, a reversible post-translational modification. For example, the mono-ADP-ribosylation of transcription factors can affect their binding to targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Additionally, these observations align with studies demonstrating that PARP‐1 and PAR are elevated in PCa compared to benign prostatic hyperplasia in a Chinese cohort (Wu et al , ) and that PARP‐1 protein is elevated in cases of primary PCa as compared to normal controls (Salemi et al , ). In other tumor types, elevated PARP‐1 mRNA is associated with poor prognosis in gliomas (Li et al , ), PARP‐1 mRNA is elevated in colon carcinoma when compared to adenoma (Dziaman et al , ), PARP‐1 gene expression is associated with lymph node spread of malignant pleural mesothelioma (Walter et al , ), and PARP‐1 mRNA and protein are elevated in endometrial adenocarcinoma (Bi et al , ). Both PARP‐1 mRNA and protein are highly expressed in small cell lung cancer (Byers et al , ), but PARP‐1 protein has been shown to associate with longer PFS in limited‐stage small cell lung cancer (Kim et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these observations align with studies demonstrating that PARP‐1 and PAR are elevated in PCa compared to benign prostatic hyperplasia in a Chinese cohort (Wu et al , ) and that PARP‐1 protein is elevated in cases of primary PCa as compared to normal controls (Salemi et al , ). In other tumor types, elevated PARP‐1 mRNA is associated with poor prognosis in gliomas (Li et al , ), PARP‐1 mRNA is elevated in colon carcinoma when compared to adenoma (Dziaman et al , ), PARP‐1 gene expression is associated with lymph node spread of malignant pleural mesothelioma (Walter et al , ), and PARP‐1 mRNA and protein are elevated in endometrial adenocarcinoma (Bi et al , ). Both PARP‐1 mRNA and protein are highly expressed in small cell lung cancer (Byers et al , ), but PARP‐1 protein has been shown to associate with longer PFS in limited‐stage small cell lung cancer (Kim et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of PARP1 itself may also determine PARP inhibitor response. PARP1 expression is increased in different cancer types, particularly at advanced stages (Ossovskaya et al 2010;Domagala et al 2011;Mascolo et al 2012;Bi et al 2013;Bieche et al 2013;Gan et al 2013;Salemi et al 2013;Dziaman et al 2014;Park et al 2015;Zhai et al 2015;Li et al 2016;Hou et al 2018), and in some cases correlates positively with the cytotoxic effects of PARP inhibition (Byers et al 2012;Kukolj et al 2017).…”
Section: Determinants Of Parp Inhibitor Sensitivity In Cancer Cellsmentioning
confidence: 99%
“…Genetic alterations of glioma have been frequently reported previously (8,9,29,30). Genetic heterogeneity across individuals has also been reported (31).…”
Section: Discussionmentioning
confidence: 72%